Growing green : a young person's guide to taking care of the planet - Goodings, Christina; Furukawa, Masumi (Oxford, England : Lion Children's, 2008)
Illustrations and text describe ways for young readers to help improve the environment, and explains why it is important; and covers conservation, recycling, compost, gardening, and more.
3.3
K-3
Keywords: Environmental protection; Sustainable living; Environmental movement